A Typology of European Values and Russians' Basic Human Values. Issue 2 (4th March 2017) - Magun, Vladimir; Rudnev, Maksim; Schmidt, Peter
Abstract : Research on social values of the Russian population usually is based on dominant or average values as reflected in public opinion surveys. The research reported in this article takes a different approach, looking not at averages but at how differences in values are distributed throughout the society. This shows a more complex picture, and one that is changing with each new generation.